Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

daltiano4l

  • 4 years ago

Solve by completing the square: 3x^2+12x+14=0

  • This Question is Closed
  1. 3pwood
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    3x^2 + 12x + 14 = 0 3(x^2 + 4x + 14/3) = 0 x^2 + 4x + 14/3 = 0 x^2 + 4x = -14/3 x^2 + 4x + (4/2)^2 = -14/3 + (4/2)^2 x^2 + 4x + 4 = -14/3 + 4 (x + 2)^2 = 4 - 14/3 x + 2 = ±sqrt(4 - 14/3) x = -2 ±sqrt(4 - 14/3)

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy